Methodological control: creation of a corpus for studies on the lexical processing of bilingual and multilingual individuals - Nalim Barbosa Pinto; Ana Beatriz Arêas da Luz Fontes (Gragoatá, 2018)
Studies about multilingual lexical access use lexical decision tasks comparing the processing of cognate and non-cognate words to investigate whether there is co-activation of languages when multilinguals process words in a single language. To understand how this process works for Portuguese-English-Italian trilinguals using a lexical decision task in Italian, a corpus was elaborated according to the following steps: selection of 1129 Italian nouns varying from 4-8 letters in length, along with their frequencies; translation of the Italian words to English and Portuguese; classification of these words as cognates in the three languages, Italian-Portuguese cognates, Italian-English cognates and non-cognates in the three languages according to an index of orthographic similarity; and classification of words according to lexical ambiguity in Italian. Homonyms were removed, leaving only polysemous and non-ambiguous words in the list.  Next, pseudowords were created from existing Italian words. After that step, the words were separated by test condition and their frequencies, length, number of syllables and orthographic similarity were compared statistically to verify their similarity. Last, the list of words to be used in the lexical decision task in Italian is composed of three test conditions of 22 cognate words each, a list of 66 non-cognate words, and a set of 132 pseudowords. This task will allow us to investigate the co-activation of English and Portuguese during lexical access in Italian.